The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsomega.0c04723
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonic-Assisted Ionic Liquid Extraction of Two Biflavonoids from Selaginella tamariscina

Abstract: Selaginella tamariscina, a traditional Chinese medicine, contains a variety of bioactive components, among which biflavonoids are the main active ingredients and have antioxidant, antitumor, and anti-inflammatory properties. In this study, ultrasonic-assisted ionic liquid extraction (UAILE) is used for the first time to extract two main biflavonoids (amentoflavone (AME) and hinokiflavone (HIN)) from S. tamariscina. A high-performance liquid chromatography method is used for the simultaneous determination of AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…After concentration and vacuum drying of the liquid, TFs were obtained and stored at 5 °C until the next analysis. As ILs are relatively sticky, according to a previous study, 57 it is found that EpyBF 4 is best soluble in a series of ethyl ethanol compounds at the same temperature, so we use ethanol to dissolve ILs. 0.1 mol/L IL concentration, 280 W of extraction power, and 12:1 mL/g of liquid/solid ratio.…”
Section: Discussionmentioning
confidence: 99%
“…After concentration and vacuum drying of the liquid, TFs were obtained and stored at 5 °C until the next analysis. As ILs are relatively sticky, according to a previous study, 57 it is found that EpyBF 4 is best soluble in a series of ethyl ethanol compounds at the same temperature, so we use ethanol to dissolve ILs. 0.1 mol/L IL concentration, 280 W of extraction power, and 12:1 mL/g of liquid/solid ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this in vitro culture system is also considered effective in generating useful functional substances of S. tamariscina, such as amentoflavone, hinokiflavone, selaginellin, etc. [23][24][25]. Moreover, this method not only could be utilized as a tool to protect plants from indiscriminate collection in their natural habitats but also as a tool to preserve the plant's habitat, and this indicates the importance of this research for preservation purposes.…”
Section: Introductionmentioning
confidence: 94%
“…Biflavonoids were a type of compound formed by the polymerization of two single flavonoids through carbon–carbon or ether-oxygen bonds and have good pharmacological activities, including antioxidant, antitumor, antibacterial and anti-inflammatory activities [8] , [9] , [10] , [11] , [12] . The previous study revealed that biflavonoids were main active ingredients in S.chaetoloma , including amentoflavone (AME), robustaflavone (ROB), hinokiflavone (HIN), and heveaflavone (HEV) [13] , [14] , [15] , [16] , [17] . The structure of the four biflavonoids appears in Fig.…”
Section: Introductionmentioning
confidence: 99%